Strategi BNI Menjadi Bank Kampus dalam Era Digital - Putri Melinda Silfiana; Adinda Martha Rahayu; Irfadella Fauzia (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Digital transformation is a process that organizations implement to integrate digital technology in all areas of business. This process influences the way organizations provide services to consumers. Digital transformation has changed the banking sector, including Bank BNI. This research analyzes the role of digital technology in BNI Mobile Banking services. With quantitative methods, data is collected through questionnaire surveys to measure user satisfaction. The results show that the majority of customers are satisfied with the service and ease of use of BNI digital facilities such as mobile banking and internet banking, which meet their needs.